LAW PROTECTION FOR INDONESIAN MIGRANT WORKERS FAMILY IN CIANJUR DISTRICT - Tanti Kirana Utami (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Cianjur as one of districts where migrant workers origin should have Local Government’s concern in terms of legal protection for both workers (TKI) and their families to achieve the family resilience and welfare. This paper examines how the protection model of TKI and their families and how its implementation. This research uses normative juridical type by case approach. This is a descriptive research by applying triangulation method. The research result shows that the model of protection for TKI and families in Cianjur district is activity programs for economic empowerment among TKI families. These programs are implemented through forming Bina Keluarga (BK-TKI)/migrant workers family programs at District level, BK-TKI at sub-district level and BK-TKI at village level. Therefore, the Migrant workers and families issue should be comprehensively and structurally conducted between government and society.Keywords: Migrant Workers Family Program, Protection Model, Economic Empowerment.